The effect of Kinesio taping on calf`s injuries prevention in triathletes during competition. Pilot experience - Merino Marban, R.; Fernández Rodriguez,E.; Iglesias Navarrete, P.; Mayorga-Vega, D. (Journal of Human Sport & Exercise, 2011)
The aim of the study was to evaluate the subjective perception of the local pain after the competition in triathletes. Before start the warm up the kinesio tape was applied in both legs through "I" technique. After the race triathletes were evaluated about perceived pain and soreness on gastrocnemius and soleos muscle by Borg's scale CR10. During the different competitions in which it was proved, none of the sportsmen suffered contractures or cramps in the musculature of the calves, and according to the scale CR10 the perceived pain was zero or not more than 2. Based on these experimental tests and properties of the kinesio tape, it is possible to recommend its use for triathletes and duathletes for injuries prevention and to avoid contractures or cramps during the competition.